Principles of renal physiology - Lote, Christopher J (New York, NY : Springer, 2012)
Annotation A good knowledge of renal physiology is essential to the understanding of many disease states. The purpose of the book is to set out the principles of renal physiology and normal renal function. Now in its 30th year of continuous publication, this new edition offers a logical progression through renal physiology and pathophysiology. In addition, the anatomy, physiology, pharmacology and pathology of the kidney are covered making it highly suitable for system based courses. This 5th edition has been extensively revised and features a wealth of new and widely accepted information about kidney function. This includes our understanding of the role of the glycocalyx and structural proteins in glomerular filtration; details of tubular transport, tight junctions and paracellular transport; and an update of the loops of Henle functioning. Principles of Renal Physiology, 5th Edition is a concise and easily readable text ideal for undergraduate medical and medical science students
The Body Fluids -- Essential Anatomy of the Kidney -- Glomerular Filtration -- Tubular Transport -- The Proximal Tubule -- The Loop of Henle, Distal Tubule and Collecting Duct -- Renal Blood Flow and Glomerular Filtration Rate -- Regulation of Body Fluid Osmolality -- Regulation of Body Fluid Volume -- Renal Regulation of Body Fluid pH -- Renal Control of Body Fluid Potassium Content -- Renal Regulation of Body Calcium, Magnesium and Phosphate -- Summary of the Principal Reabsorptive and Secretory Processes in the Nephron Segments -- Disease Conditions Which Alter Renal Sodium and Water Reabsorption -- Use of Diuretics
Includes bibliographical references and index.
Keywords: Kidney -- physiology; Renal Circulation -- physiology; Nephrology